Impact of COVID-19 on Patients Supported with a Left Ventricular Assist Device. Issue 11 (1st September 2021) - Zakrzewski, Jack; Coyle, Laura; Aicher, Tracy; Chickerillo, Krystina; Gallagher, Colleen; Kuper, Katelyn; Sciamanna, Chris; Chau, Vinh Q.; Tatooles, Antone
Abstract : Supplemental Digital Content is available in the text. Abstract : Patients on left ventricular assist device (LVAD) support may be susceptible to severe disease and complications from coronavirus disease-19 (COVID-19). The purpose of this study was to describe the clinical course of COVID-19 in LVAD patients. A retrospective review was performed at our center; 28 LVAD patients who developed COVID-19 between March 2020 and March 2021, and six patients with a prior COVID-19 infection who underwent LVAD implantation, were identified and examined. Of the 28 patients, nine (32%) died during the study period, five (18%) during their index hospitalization for COVID-19. Two patients (7%) presented with suspected pump thrombosis. In a nonadjusted binary regression logistic analysis, admission to the intensive care unit (unadjusted odds ratio, 7.6 [CI, 1.2–48], P = 0.03), and the need for mechanical ventilation (unadjusted odds ratio 14 [CI, 1.3–159], P = 0.03) were associated with mortality. The six patients who previously had COVID-19 and subsequently received a LVAD were on intra-aortic balloon pump and inotropic support at time of surgery. All six experienced a complicated and prolonged postoperative course. Three patients (50%) suffered from ischemic stroke, and there was one (17%) 30 day mortality. We observed an increased risk of morbidity and mortality in LVAD patients with COVID-19.